2015
DOI: 10.1002/jms.3714
|View full text |Cite
|
Sign up to set email alerts
|

Linear ion trap with added octopole field component: the property and method

Abstract: It is well known that superimposition of some positive octopole field will benefit the performance of ion trap mass analyzer. In the radial-ejection linear ion trap (LIT), adding some octopole field component to the main quadrupole field is usually accomplished by stretching the ejection rod pair. In this study, the effect of octopole potential and some other higher order potential on the performance of LIT mass analyzer is investigated. A simple and effective method, which is to add some octopole component by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…An ion trap using a hyperboloid electrode can generate an ideal quadrupolar field, and modifications to the electrode structure will introduce other multipolar field components. Previous studies have found that high‐order field components are one of the key factors affecting the performance of ion trap resolution and collision efficiency 27–29 . Further analysis of the multipolar component of the electric field in the trap is performed, and the results are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…An ion trap using a hyperboloid electrode can generate an ideal quadrupolar field, and modifications to the electrode structure will introduce other multipolar field components. Previous studies have found that high‐order field components are one of the key factors affecting the performance of ion trap resolution and collision efficiency 27–29 . Further analysis of the multipolar component of the electric field in the trap is performed, and the results are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Note that traps with both axial and radial symmetry generally only contain even-order fields in which ion secular frequencies will increase with the radial distance for a positive field contribution [85,86]. The corresponding effect on mass spectral performance with resonance ejection is that, for traps with positive even-order fields, resolution is increased when scanning the rf amplitude from low to high, but decreased when scanning from high to low, as shown in Figure 4b [87][88][89]. This is because as ions are brought to the resonance ejection working point, they increase their amplitudes in the trap.…”
Section: Effect Of Higher-order Fields On Mass Analysismentioning
confidence: 99%
“…21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Notesunclassified
“…This has been implemented in SIMION, [11][12][13] ITSIM, [13][14][15][16] ISIS, 13,17 and some other home written simulation programs. [18][19][20][21] Our recent study, however, has shown that the flowing motion of the gas molecules at pressures as low as 10 -5 Torr could have a significant impact on the trapping of the ions. 22 At pressures of 1 Torr and higher, collisions occur more frequently.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation